Comparison of sandstone Mechanic properties using acoustic test and direct uniaxial test - Samsuri, Ariffin; Herianto, Herianto (2004)
Rock mechanical characterization usually can be done through direct test with uniaxial or triaxial test by equipment of compression unit. The velocity of ultrasonic wave with compressional (P) wave and shear (S) wave can be used to determine the value of rock mechanical characteristic such as Poisson Ratio and Young Modulus. In this study, two methods had been used for sandstone sample. By knowing the correction factor of a rock taken from a specific location, one can determine the rock mechanical properties of the rock from the same location without destructing the rock due to testing.